1984
DOI: 10.3109/14017438409102391
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Activated Coagulation Time in Monitoring Heparin Therapy During Extracorporeal Circulation

Abstract: The anticoagulant effect of heparin was studied in 20 patients undergoing aortocoronary bypass surgery. The protamine dose necessary to reverse heparin after extracorporeal circulation (ECC) was assessed in ten patients from individual heparin dose-response curves (HDR group). The other ten patients received protamine according to a routine protocol (control group). The protamine administration was followed in both groups by injection of 3-5 g tranexamic acid (Cyklokapron). A wide range of sensitivity to hepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

1990
1990
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…Six previous reports provide both prebypass and postprotamine ACT values (5,6,[9][10][11]22). Only two of these clearly obtained the prebypass ACT before inducing anesthesia, and both found postprotamine ACT values significantly below preinduction ones (9,ll).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Six previous reports provide both prebypass and postprotamine ACT values (5,6,[9][10][11]22). Only two of these clearly obtained the prebypass ACT before inducing anesthesia, and both found postprotamine ACT values significantly below preinduction ones (9,ll).…”
Section: Discussionmentioning
confidence: 99%
“…Only two of these clearly obtained the prebypass ACT before inducing anesthesia, and both found postprotamine ACT values significantly below preinduction ones (9,ll). Kamath and Fozard showed nearly equal ACTs before CPB and after protamine (5); other investigators found postprotamine ACTs higher than pre-CPB values (6,22). Kamath and Fozard showed nearly equal ACTs before CPB and after protamine (5); other investigators found postprotamine ACTs higher than pre-CPB values (6,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Τα πρωτόκολλα παρακολούθησης µπορούν σηµαντικά να επηρεάσουν τις δόσεις πρωταµίνης που χρειάζονται για να εξουδετερώσουν την ηπαρίνη [510,518,[522][523][524][525][526][527]. ∆ύο πρόσφατες µελέτες σύγκριναν τη χρήση ενός νέου διαγνωστικού αιµοστατικού συστήµατος (RxDx System, International Technidyne, Edison, New Jersey) µε το πρότυπο ACT βασισµένο σε εµπειρικό σχήµα στους ενήλικες ασθενείς που υπεβλήθησαν σε καρδιοχειρουργικές επεµβάσεις [518,527].…”
Section: είναι λογική η χρήση είτε τιτλοποιηµένης πρωταµίνης είτε εµπunclassified
“…[527] δεν παρατήρησαν µείωση στην απώλεια αίµατος και στις απαιτήσεις για µετάγγιση, ούτε σηµαντική µείωση στη δόση της πρωταµίνης µε τη χρήση του συστήµατος RxDx. Από οκτώ δηµοσιευµένες µελέτες που συγκεκριµένα µελέτησαν την κλινική επίδραση της µειωµένης δόσης πρωταµίνης, τέσσερις ανέδειξαν είτε µειωµένη απώλεια αίµατος ή απαιτήσεις σε µετάγγιση [588,[522][523][524], και τέσσερις όχι [510,[525][526][527]. Η αντίφαση στο αποτέλεσµα µεταξύ των µελετών πιθανόν σχετίζεται µε διαφορές στη σχετική έκταση της µείωσης της δόσης της πρωταµίνης και στη συνολική αναλογία πρωταµίνης-ηπαρίνης στην οµάδα παρέµβασης.…”
Section: είναι λογική η χρήση είτε τιτλοποιηµένης πρωταµίνης είτε εµπunclassified